GAS CHROMATOGRAPHY-MASS SPECTROSCOPY STUDIES ON ETHANOLIC EXTRACT OF DRIED LEAVES OF CATHARANTHUS ROSEUS - Doshi, Gaurav M; Matthews, Bernadette D; Chaskar, Pratip K (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: Phytochemical screening of the ethanolic extract of Catharanthus roseus disclosed the presence of alkaloids, terpenoids, phenols, tannins, saponins, quinines, flavonoids, and proteins. In the present research work, we have identified and confirmed the structures of the constituents present by means of a hyphenated technique of gas chromatography-mass spectrometry (GC-MS) from the extract. Method: Shade-dried leaves of C. roseus were powdered and extracted by means of Soxhlet extraction using ethanol as a solvent. Crude extract obtained was utilized for GC-MS. Results: A total of 15 components were identified, some of which were n-hexadecanoic acid, ethyl ester, Vitamin E, 9,12,15-octadecatrienoic acid,2- [(trimethylsilyl)oxy]-1-[{(trimethylsilyl)oxy}methyl]ethyl ester, phytol, 3-epivindolinine, and oleic acid. Conclusion: GC-MS studies helped us to assess the phytochemical constituents based on retention time, molecular formula, molecular weight and the corroboration of MS libraries. In future, C. roseus leaves may be subjected to diverse types of extraction methodologies, and a number of various elucidated phytoconstituents can be studied for their ethnopharmacological significance and applicability citing literature.